1997
DOI: 10.1590/s1516-31801997000300011
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical study of the renal veins observed during 342 living-donor nephrectomies

Abstract: The anatomical variations of renal veins observed during 342 nephrectomies in living donors are described, 311 cases on the left side and 31 on the right. The following anatomy of the renocava veins was observed: 1. On the left side the renal vein was always unique (311/311) and had two tributaries (suprarenal and gonadal veins) in 100 per cent and one or more renolumbar veins in 65.27 per cent, encircling the aorta in 1.07 per cent, was retroaortic in 1.4 per cent; and the inferior vena cava was double in 0.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
39
1
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 1 publication
3
39
1
3
Order By: Relevance
“…An error of fusion of these two vessels, thus causing their persistence, may result in bilateral or unilateral duplication of these vessels [10]. Occurrences of multiple renal veins are relatively common, and several authors have reported large numbers of venous variations resulting from embryonic developmental errors [1], [5], [11][12][13]. According to Kaneko, Kobayashi and Okada [14], the renal veins present fewer variations than do the renal arteries, and multiple renal veins are more common on the right side than on the left-sid [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An error of fusion of these two vessels, thus causing their persistence, may result in bilateral or unilateral duplication of these vessels [10]. Occurrences of multiple renal veins are relatively common, and several authors have reported large numbers of venous variations resulting from embryonic developmental errors [1], [5], [11][12][13]. According to Kaneko, Kobayashi and Okada [14], the renal veins present fewer variations than do the renal arteries, and multiple renal veins are more common on the right side than on the left-sid [8].…”
Section: Discussionmentioning
confidence: 99%
“…Because the right kidney is closer to the interior vena cava, the right renal vein is generally shorter and rarely receives tributaries. On the other hand, the left renal vein, which is longer, may receive several tributaries [1], [2]. Variations in the origin, path and termination of the renal veins, along with vascular malformations that are found in the renal hilum involving both arteries and veins, result mainly from errors of embryonic development [3], [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It describes a horizontal course toward the inferior vena cava, in which it drains. In literature, a significant prevalence of anatomical variations on the left renal vein (about 92%) was found (Baptista-Silva et al, 1997), and the presence of multiple right renal veins (more than 2 vessels) was found in about 8,0 to 9,7% of cases (Baptista-Silva et al). On the other hand, Bergman et al, pointed that, the renal veins show less variation than do the renal arteries and multiple renal veins to be rare on the left side (1%) and common on the right side (28%).…”
mentioning
confidence: 99%
“…Bu sorunlar genellikle greft nefrektomi veya nakli sıra-sında travma ile ilgilidir. Güçlüklerin sağ böbrek ile ortaya çık-ması, sağ renal venin daha kısa ve anatomik varyasyonlarının sol tarafa göre daha sık olmasından dolayı daha olasıdır [2,5]. Bizim olgumuzda da, donör sağ renal venin yaralanmış olmasın-dan dolayı teknik zorlukla karşılaştık.…”
Section: Discussionunclassified